Genetic and antigenic evolution profiles of G1 rotaviruses in córdoba, Argentina, during a 27-year period (1980-2006) - Barril, Patricia Angelica (2013)
Rotavirus G1 strains represent the most common genotype that causes diarrhea in humans and has been incorporated into both, monovalent and multivalent, rotavirus licensed vaccines. The aim of this study was to determine the evolution profile of G1 rotaviruses in Córdoba, Argentina, over a 27-year period (1980-2006). Intragenotype diversity, represented by lineages within rotavirus circulating strains, was observed. Phylogenetic analysis of the VP7-gene of G1 rotavirus clinical strains showed the circulation of G1 lineage IV and V strains in the 1980s, and co-circulation of lineage I and II strains in the 1990s and 2000-2006. The distribution of G1 in lineages could be linked to multiple nucleotide substitutions distributed across lineages that did not correlate with the emergence of G1 antigenic variants. Moreover, temporal lineage distribution was not linked to significant changes in G1 prevalence. Therefore, the continuous and dominant circulation of G1 over time could not be related to the emergence of antigenic variants in the community. Continuous rotavirus surveillance is necessary to understand rotavirus evolution and to measure how genetic and antigenic changes might affect the effectiveness of vaccines in the future.